Microalgal Carbon Dioxide (CO2) Capture and Utilization from the European Union Perspective - Marcin Zieliński; Marcin Dębowski; Joanna Kazimierowicz; Izabela Świca (Energies, 2023)
The increasing concentration of anthropogenic CO2 in the atmosphere is causing a global environmental crisis, forcing significant reductions in emissions. Among the existing CO2 capture technologies, microalgae-guided sequestration is seen as one of the more promising and sustainable solutions. The present review article compares CO2 emissions in the EU with other global economies, and outlines EU’s climate policy together with current and proposed EU climate regulations. Furthermore, it summarizes the current state of knowledge on controlled microalgal cultures, indicates the importance of CO2 phycoremediation methods, and assesses the importance of microalgae-based systems for long-term storage and utilization of CO2. It also outlines how far microalgae technologies within the EU have developed on the quantitative and technological levels, together with prospects for future development. The literature overview has shown that large-scale take-up of technological solutions for the production and use of microalgal biomass is hampered by economic, technological, and legal barriers. Unsuitable climate conditions are an additional impediment, forcing operators to implement technologies that maintain appropriate temperature and lighting conditions in photobioreactors, considerably driving up the associated investment and operational costs.